ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INDEKS KUALITAS LINGKUNGAN HIDUP (IKLH) DI INDONESIA TAHUN 2017-2019 - Awwalina Zulfa Hidayati (Jurnal Medika Hutama, 2022)
Environmental quality is defined as environmental conditions that can provide optimal support for human survival in an area. The decrease in environmental quality is not only caused by excessive use of natural resources, but also as a result of community activities, uncontrolled population growth and poor quality of human resources. Based on previous research, the quality of the environment is influenced by several factors such as health, environment, politics and economy. Indonesia uses the term Environmental Quality Index (IKLH), which is an initial description or indication that provides a quick conclusion of an environmental condition in a certain scope and period. This study aims to analyze the factors that affect the Environmental Quality Index (IKLH) in Indonesia in 2017-2019. The study design used is an ecological study based on time (time trend) with a provincial unit of analysis. The population and sample of this study were all provinces in Indonesia, which amounted to 34 provinces. Research data sources come from the Ministry of Environment and Forestry (KLHK) and the Central Statistics Agency (BPS). The results of statistical tests show a significant relationship between population density, HDI and land transportation with IKLH in Indonesia in 2017-2019 (p <0.05) with r values of 0.794; 0.529 and 0.666 (2017); -0.801; -0.539 and -0.729 (in 2018) and -0.824; -0.583 and -0.741 (in 2019). Population Density and Land Transportation have an influence on IKLH in Indonesia in 2017-2019 and the biggest influence is Population Density. The central and local governments are expected to re-invigorate population control programs and develop cheap and adequate public transportation.